Prevalence and associated factors of client satisfaction with family planning service among family planning users in Ethiopia: a systematic review and meta-analysis - Temesgen Geta; Nefsu Awoke; Tadele Lankrew; Eshetu Elfios; Eskinder Israel (BMC Women's Health, 2023)
Abstract Background Considering the importance of client satisfaction in the quality of family planning services, a regular evaluation should be carried out. Several studies have been conducted in Ethiopia, but so far there were no pooled estimates of the prevalence of customer satisfaction with family planning services in the country. Therefore, this systematic review and meta-analysis was intended to estimate the pooled prevalence of client satisfaction with Ethiopian family planning services in Ethiopia. The findings of the review can be used to develop strategies and draft policies in the country. Methods and materials This review included articles published only in Ethiopia. The main databases were Medline/PubMed, Web of Science, Google Scholar, Scopus, Ethiopian University Repository Online, and Cochrane Library. Cross-sectional studies conducted in English and meeting the eligibility criteria were included in the review. A random-effects meta-analysis was performed. Data extraction and analysis were performed using Microsoft Excel and STATA version 14 software, respectively. Result The pooled prevalence of customer satisfaction with family planning services in Ethiopia was 56.78% [(95% CI (49.99, 63.56); I2 = 96.2%, p < 0.001]. Waiting time > 30 min [OR = 0.2, 95% CI (0.1–0.29), I2 = 75.0%, p < 0.001], privacy maintained [OR = 5.46, 95% CI (1.43–20.9), I2 = 95.8%, p < 0.001], education status [OR = 0.47], 95% CI (0.22–0.98), I2 = 87.4%, p < 0.001] was significant in client satisfaction related to family planning services. Conclusion According to this review, client satisfaction with family planning services in Ethiopia was 56.78%. In addition, waiting time, women's educational level, and respect for privacy were identified as factors that both positively and negatively impact women's satisfaction with family planning services. Decisive action, such as educational intervention, continued monitoring and evaluation of family planning services, and arranging training for providers, is required to address identified issues and ensure higher levels of family satisfaction and utilization. This finding is important for shaping strategic policies and improving the quality of family planning services. This finding is important for designing strategic policy and increasing the quality of family planning services.